Acoustic Doppler profiler measurements and CFD validation for Tucurui hydro power plant tailrace flow investigation. (August 2019) - Bortoni, Edson C.; Santos, Luciano T.; Bertrand, Olivier; Sauvaget, Patrick
Abstract: Tucurui hydro power plant was constructed with two tailraces referring to phases I and II. The bed of the tailrace related to phase II has a high bank and a curvature oriented towards the right. Overall dynamics points to the potential existence of local circulation, which can produce adverse pressure in front of some units. With the objective of validating this hypothesis, a CFD model was developed to describe this tailrace. A survey of measurements using an acoustic Doppler profiler device was conducted in order to adjust and to validate the developed CFD model. This paper states the original problem, the main adoptions in the CFD modeling, the obtained results from the measurements, allowing for comparison between the physical and numerical approach, and the simulation of several other operational conditions. Graphical abstract: Image 1 Highlights: Flow profile investigation at Tucurui hydro power plant tailrace. Application of acoustic Doppler current profiler. Modeling, Simulation, and validation of CFD software results.